Preoperative 2-[18F]FDG PET-CT aids in the prognostic stratification for patients with primary ampullary carcinoma - Chuang, Pei-Ju; Wang, Hsiu-Po; Lin, Yu-Jen; Chen, Chieh-Chang; Tien, Yu-Wen; Hsieh, Min-Shu; Yang, Shih-Hung; Yen, Ruoh-Fang; Ko, Chi-Lun; Wu, Yen-Wen; Cheng, Mei-Fang (European radiology, 2021)
Objectives We sought to investigate whether preoperative dual-phase 2-[ 18 F]FDG PET-CT identify predictors for poor survival in patients with ampullary carcinoma receiving pancreaticoduodenectomy. Methods The preoperative PET-CT images of patients with resected ampullary carcinoma from June 2007 to July 2017 were analyzed. Survival curves were analyzed using the Kaplan-Meier method and compared with the log-rank test. Cox proportional hazard model was used to identify potential prognostic factors associated with disease-free survival (DFS) and overall survival (OS). Results Fifty-four subjects (26 men, 28 women) were enrolled with a median tumor size of 20 mm. All patients were followed for a median period of 36.9 months with 3- and 5-year DFS of 50.3% and 44.2%, and OS of 77.0% and 68.2%, respectively. Parameters associated with DFS in multivariate analysis were lymphovascular invasion (hazard ratio [HR]: 9.45, p < 0.001), involved margin in pathology (HR: 7.67, p < 0.001), and tumor retention index (RI) from the dual-phase PET (HR: 2.41, p = 0.03), whereas involved margin (HR: 13.14, p < 0.001), post-recurrence chemotherapy (HR: 0.10, p < 0.001), and metabolic tumor volume (MTV) (HR: 4.62, p = 0.009) emerged as independent prognostic factors for OS. Conclusions Preoperative 2-[ 18 F]FDG PET-CT offered independent prognostic biomarkers in patients with ampullary carcinoma receiving standard surgical resection. Key Points • 2-[ 18 F]FDG PET-CT offers good survival prediction before operation in primary malignant neoplasms at ampulla of Vater. • Dual-phase PET scan with bowel distention can better delineate Ampulla of Vater and characterize tumor physiology. • Preoperative risk stratification might aid in better treatment planning.